TRADISI TULIS ULAMA KERINCI: MANUSKRIP ISLAM PENINGGALAN K.H MUHAMMAD BURKAN SALEH - Oga Satria; Rasidin, MHD (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2020)
This paper explores the works of K.H. Muhammad Burkan Saleh (1912-2010) as one of the Kerinci scholars who was productive wrote his works. Initially, the manuscripts found in Kerinci contained more traditional issues written in the Incung script and discussed very little on religious issues. The Kerinci manuscript, which contains religious themes, was only written in the late 19th century. This study is a qualitative study that focuses on the text domain and context. In addition, the authors also conducted interviews with manuscript collectors and their families to obtain data related to the manuscript descriptions and biographies of K.H. Muhammad Barkan Saleh. This paper shows that the tradition of writing among the Kerinci ulama continued until the 20th century as practiced by K.H Muhammad Burkan Saleh who wrote some of the information obtained using Arabic and Malay Arabic characters. The discussion themes he wrote also varied, such as the issue of Musṭalaḥ al-Ḥadîṡ, the knowledge of the Koran, the science of astronomy, he even wrote things related to amulets. Keywords: Kerinci, K.H Muhammad Burkan Saleh, manuscript. Tulisan ini mengeksplorasi karya-karya K.H. Muhammad Burkan Saleh (1912-2010) sebagai salah satu ulama Kerinci yang produktif menulis karya-karyanya. Pada awalnya naskah-naskah yang ditemukan di Kerinci lebih banyak memuat permasalahan-permasalahan adat yang ditulis dengan menggunakan aksara Incung dan sangat sedikit membicarakan persoalan keagamaan. Manuskrip Kerinci yang memuat tema keagamaan baru ditulis pada akhir abad ke-19. Kajian ini merupakan penelitian kualitatif yang terfokus pada domain teks dan konteks. Selain itu, penulis juga melakukan wawancara dengan kolektor manuskrip dan keluarga untuk memperoleh data terkait deskripsi manuskrip dan biografi K.H. Muhammad Barkan Saleh. Tulisan ini menunjukkan bahwa tradisi tulis di kalangan ulama Kerinci masih terus berlanjut hingga abad ke-20 sebagaimana yang dilakukan oleh K.H Muhammad Burkan Saleh yang menulis beberapa informasi yang diperoleh mengunakan aksara Arab dan Arab Melayu. Tema pembahasan yang ia tulis pun beragam, seperti persoalan Musṭalaḥ al-Ḥadîṡ, ilmu Al-Qur’an, ilmu falak, bahkan ia juga menulis hal-hal yang berkaitan dengan azimat. Kata Kunci: Kerinci, K.H Muhammad Burkan Saleh, manuskrip.